Exostoma sentiyonoae, a new catfish (Teleostei: Sisoridae) from Nagaland, Northeastern, India - Shangningam, Bungdon; Limatemjen (Zootaxa, 2024)
Exostoma sentiyonoae, a new species of glyptosternine catfish is described from the Dzuleke River, a tributary of the Barak River in Nagaland, northeastern India. This is the fourth species of Exostoma described from the Barak drainage. The new species can be distinguished from congeners by the adipose fin adnate to the upper procurrent caudal-fin rays, presence of tubercles on dorsal-fin spine, anterolateral surfaces of lip with parallel and rounded striae, slender head 7.7–13.1% SL, long dorsal-adipose distance 16.8–24.6% SL, small eye 5.1–8.8 % HL, and 41 vertebrae. Two species groups within the genus Exostoma are proposed; Group I, in which the adipose fin is confluent with the upper procurrent caudal-fin rays, and Group II in which adipose fin is separate from the upper procurrent caudal-fin rays.